Bendamustine is a safe and effective lymphodepletion agent for axicabtagene ciloleucel in patients with refractory or relapsed large B-cell lymphoma - Crystal Mackall; Holden T Maecker; Lekha Mikkilineni; Melody Smith; Saurabh Dahiya; Bita Sahaf; David Miklos; Sally Arai; Surbhi Sidana; Wen-Kai Weng; Dasom Lee; Anmol Goyal; et al. (Journal for ImmunoTherapy of Cancer)
Background Fludarabine in combination with cyclophosphamide (FC) is the standard lymphodepletion regimen for CAR T-cell therapy (CAR T). A national fludarabine shortage in 2022 necessitated the exploration of alternative regimens with many centers employing single-agent bendamustine as lymphodepletion despite a lack of clinical safety and efficacy data. To fill this gap in the literature, we evaluated the safety, efficacy, and expansion kinetics of bendamustine as lymphodepletion prior to axicabtagene ciloleucel (axi-cel) therapy.Methods 84 consecutive patients with relapsed or refractory large B-cell lymphoma treated with axi-cel and managed with a uniform toxicity management plan at Stanford University were studied. 27 patients received alternative lymphodepletion with bendamustine while 57 received FC.Results Best complete response rates were similar (73.7% for FC and 74% for bendamustine, p=0.28) and there was no significant difference in 12-month progression-free survival or overall survival estimates (p=0.17 and p=0.62, respectively). The frequency of high-grade cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome was similar in both the cohorts. Bendamustine cohort experienced lower proportions of hematological toxicities and antibiotic use for neutropenic fever. Immune reconstitution, as measured by quantitative assessment of cellular immunity, was better in bendamustine cohort as compared with FC cohort. CAR T expansion as measured by peak expansion and area under the curve for expansion was comparable between cohorts.Conclusions Bendamustine is a safe and effective alternative lymphodepletion conditioning for axi-cel with lower early hematological toxicity and favorable immune reconstitution.